Exergy Analysis of Power Plants That Utilize Waste Heat from Cement Plants in West Sumatera - Heroza, Nadry; Pratoto, Adjar (Universitas Mercu Buana, 2025)
Exergy analysis of power plants that utilize exhaust heat at Cemen plant was carried out to identify the reliability of the generator as a whole system or for each component that could be used as a basis for optimizing the utilization of exhaust heat and optimizing the operation of the generator to make it more efficient with increasing usage life. The exergy flow and efficiency are calculated for each component, and the data is then used to calculate how much exergy is destroyed in each component. Calculations are also carried out on the system at the time of commissioning in order to get how much the exergy efficiency has changed since the system was operational. The components of this plant include an SP boiler, AQC boiler, turbine, condenser, condensate pump, Flasher, boiler feed pump, and economist. AQC boiler is the component with the highest exergy value that is destroyed, which is 4405.34 kW or 32.98% of the total exergy destroyed in the system. The condensate pump is the component that has the smallest destroyed exergy value of 18.94 kW (0.14%). The system efficiency in January 2012 was 62.60% and decreased in December 2019 to 53.04%, where the overall system exergy efficiency decreased by 9.56% within 7 years of operation.